Effectiveness of web-based interventions for women with urinary incontinence: protocol for a systematic review and meta-analysis of randomised controlled trials - Hongyan Wang; Ping Xu; Wei Zhang; Ying Jin; Xiaojuan Wang; Dan Dan Chen; Weijing Chen; Pingping Guo; Minna Mao; Suwen Feng; Rujia Zhao; Xuefen Xu; et al. (BMJ Open)
Introduction Urinary incontinence (UI) is one of the most common chronic diseases among women, which can endanger their physical and mental health and incur a heavy financial burden on both individuals and society. Web-based interventions (WBIs) have been applied to manage women’s UI, but their effectiveness has remained inconclusive. This systematic review and meta-analysis aims to explore the effectiveness of WBIs on self-reported symptom severity, condition-specific quality of life, adherence to pelvic floor muscle training (primary outcomes) and other extensive secondary outcomes among women with UI. We also aimed to investigate whether intervention characteristics (format, interactivity and main technology) have impacts on the effectiveness of primary outcomes.Methods and analysis This systematic review protocol was developed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines. 10 electronic databases will be comprehensively searched from their inception to 1 May 2024, along with grey literature searches and manual reviews of relevant reference lists to identify eligible randomised controlled trials. The methodological quality of the included studies will be assessed by two reviewers based on the Cochrane Risk of Bias Tool. Meta-analyses will be conducted via Stata V.12.0. Leave-one-out sensitivity analyses will be performed, and publication bias will be evaluated using funnel plots and Egger’s test. Subgroup analyses regarding intervention format, interactivity and main technology will be carried out.Ethics and dissemination No ethics approval is needed for this review since no primary data are to be collected. The results of this review will help develop an optimal WBI for women with UI, thereby providing them with maximum benefits. The findings will be disseminated via a peer-reviewed journal or conference presentation.PROSPERO registration number CRD42023435047.